Tauroursodeoxycholic acid alleviates pulmonary endoplasmic reticulum stress and epithelial-mesenchymal transition in bleomycin-induced lung fibrosis - Tong, Bin (BMC Pulm Med, 2021)
BACKGROUND: Several studies demonstrate that endoplasmic reticulum (ER) stress-mediated epithelial-mesenchymal transition (EMT) is involved in the process of bleomycin (BLM)-induced pulmonary fibrosis. Tauroursodeoxycholic acid (TUDCA), a bile acid with chaperone properties, is an inhibitor of ER stress. This study aimed to investigate the preventive effects of TUDCA on BLM-induced EMT and lung fibrosis. METHODS: The model of lung fibrosis was established by intratracheal injection with a single dose of BLM (3.0 mg/kg). In TUDCA + BLM group, mice were intraperitoneally injected with TUDCA (250 mg/kg) daily. RESULTS: BLM-induced alveolar septal destruction and inflammatory cell infiltration were alleviated by TUDCA. BLM-induced interstitial collagen deposition, as determined by Sirius Red staining, was attenuated by TUDCA. BLM-induced elevation of pulmonary α-smooth muscle actin (α-SMA) and reduction of pulmonary E-cadherin were attenuated by TUDCA. BLM-induced pulmonary Smad2/3 phosphorylation was suppressed by TUDCA. BLM-induced elevation of Ki67 and PCNA was inhibited by TUDCA in mice lungs. In addition, BLM-induced elevation of HO-1 (heme oxygenase-1) and 3-NT (3-nitrotyrosine) was alleviated by TUDCA. Finally, BLM-induced upregulation of pulmonary GRP78 and CHOP was attenuated by TUDCA. CONCLUSIONS: These results provide evidence that TUDCA pretreatment inhibits Smad2/3-medited EMT and subsequent lung fibrosis partially through suppressing BLM-induced ER stress and oxidative stress. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12890-021-01514-6.